2016
DOI: 10.1186/s12888-016-1142-9
|View full text |Cite
|
Sign up to set email alerts
|

Smoking in pregnancy, adolescent mental health and cognitive performance in young adult offspring: results from a matched sample within a Finnish cohort

Abstract: BackgroundThe association between prenatal exposure to maternal cigarette smoking (PEMCS) and adult cognition is debated, including if there are differences according to sex. We aimed to determine if there are associations between PEMCS and cognition in early adulthood in men and women and examine if observed associations were mediated by adolescent mental health factors that are associated with cognition, namely psychotic-like experiences (PLEs), inattention and hyperactivity, and other externalizing behavior… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 55 publications
0
14
0
Order By: Relevance
“…Considerable evidence suggests that maternal smoking while pregnant is associated with various adverse offspring outcomes across developmental periods, including antisocial behaviour and offending (Pratt, McGloin, & Fearn, 2006;Wakschlag, Pickett, Cook, Benowitz, & Leventhal, 2002), other externalising problems (Linnet et al, 2003), internalising problems (Ashford, Van Lier, Timmermans, Cuijpers, & Koot, 2008), and poor cognitive performance (Ramsay et al, 2016). While several studies have identified a dose-response relationship between prenatal smoking and adverse offspring outcomes (Moylan et al, 2015;Obel et al, 2009) that may be consistent with a causal relationship, other large population-based studies have failed to find a causal relationship or observed that other family factors strongly influenced the relationship between prenatal smoking and offspring outcomes-such as severe mental illness (Quinn et al, 2017), externalising problems (Roza et al, 2009;Skoglund, Chen, Lichtenstein, & Larsson, 2014), internalising problems (Meier et al, 2017), and poor cognitive and physical development (Gilman, Gardener, & Buka, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Considerable evidence suggests that maternal smoking while pregnant is associated with various adverse offspring outcomes across developmental periods, including antisocial behaviour and offending (Pratt, McGloin, & Fearn, 2006;Wakschlag, Pickett, Cook, Benowitz, & Leventhal, 2002), other externalising problems (Linnet et al, 2003), internalising problems (Ashford, Van Lier, Timmermans, Cuijpers, & Koot, 2008), and poor cognitive performance (Ramsay et al, 2016). While several studies have identified a dose-response relationship between prenatal smoking and adverse offspring outcomes (Moylan et al, 2015;Obel et al, 2009) that may be consistent with a causal relationship, other large population-based studies have failed to find a causal relationship or observed that other family factors strongly influenced the relationship between prenatal smoking and offspring outcomes-such as severe mental illness (Quinn et al, 2017), externalising problems (Roza et al, 2009;Skoglund, Chen, Lichtenstein, & Larsson, 2014), internalising problems (Meier et al, 2017), and poor cognitive and physical development (Gilman, Gardener, & Buka, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Epidemiological studies have discovered the link between maternal cigarette smoking during pregnancy and the alteration in neurocognitive functions in the offspring (eg. schizophrenia) . Size matters, which applies well with cognitive performance.…”
Section: Maternal Cigarette Smoking and Neurocognitive Outcomesmentioning
confidence: 95%
“…schizophrenia). [13][14][15][16] Size matters, which applies well with cognitive performance. In both human offspring from smoking mothers and rodent offspring from SE dams, reduced offspring's brain size including reduced cerebral cortical gray matter and total parenchymal volume, as well as cerebellum and corpus callosum volume/thickness.…”
Section: Maternal Cig Are T Te S Moking and Neurocog Nitive Outcome Smentioning
confidence: 99%
“…Commonly reported behavioral symptoms include impulsive, disruptive, and inattentive behaviors, learning difficulties, affective symptoms and reduced IQ (Clifford, Lang, & Chen, ; Gaysina et al, ; Kovess et al, ). In addition, children with fetal tobacco exposure show elevated risk for psychiatric issues, including attention deficit hyperactivity disorder (ADHD) and conduct disorder (Han et al, ; Ramsay et al, ; Talati, Wickramaratne, Wesselhoeft, & Weissman, ). Although the association between maternal smoking and offspring behavior has been well demonstrated, many questions remain as to the exact mechanisms by which tobacco smoke impacts the developing brain.…”
Section: Introductionmentioning
confidence: 99%
“…An error was subsequently identified. This notice is included in the online and print versions to indicate that both have been corrected 16 August 2019. deficit hyperactivity disorder (ADHD) and conduct disorder (Han et al, 2015;Ramsay et al, 2016;Talati, Wickramaratne, Wesselhoeft, & Weissman, 2017). Although the association between maternal smoking and offspring behavior has been well demonstrated, many questions remain as to the exact mechanisms by which tobacco smoke impacts the developing brain.…”
Section: Introductionmentioning
confidence: 99%